2014
DOI: 10.2478/pjvs-2014-0065
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro effect of kynurenic acid on the rainbow trout (Oncorhynchus mykiss) leukocyte and splenocyte activity

Abstract: Kynurenic acid (KYNA), an endogenous neuroprotectant formed along the kynurenine pathway of tryptophan degradation, is a selective ligand of the GPR35 receptor, which can be found on the surface of various populations of human immune cells. In infections and inflammations, KYNA produces an anti-inflammatory effect through this receptor, by depressing the synthesis of reactive oxygen species and pro-inflammatory cytokines. However, it is still unrecognized whether receptors for kynurenic acid are also localized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The obtained results are broadly in line with the results from our previous experiments conducted on immune cells isolated from the peripheral blood and spleen of rainbow trout, as well as on several types of cells unrelated to the immune system (NIH-3T3 mouse fibroblasts, GMK green monkey kidney cells, CECC chick embryo cells). In all the above-mentioned studies, KYNA concentrations up to 1 mM were well tolerated by the cells [ 20 , 21 ]. Furthermore, a certain proliferative effect noted at the lowest concentration of KYNA remains in compliance with the literature reports and our previously conducted studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The obtained results are broadly in line with the results from our previous experiments conducted on immune cells isolated from the peripheral blood and spleen of rainbow trout, as well as on several types of cells unrelated to the immune system (NIH-3T3 mouse fibroblasts, GMK green monkey kidney cells, CECC chick embryo cells). In all the above-mentioned studies, KYNA concentrations up to 1 mM were well tolerated by the cells [ 20 , 21 ]. Furthermore, a certain proliferative effect noted at the lowest concentration of KYNA remains in compliance with the literature reports and our previously conducted studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a certain proliferative effect noted at the lowest concentration of KYNA remains in compliance with the literature reports and our previously conducted studies. Low, micromolar KYNA concentrations stimulated the proliferation of fish splenocytes [ 20 ], chick embryo fibroblasts, green monkey kidney cells [ 21 ], and human and murine glial cells [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… and Małaczewska et al . ). This observation seems to confirm the above hypothesis that KYNA can be a toxic or stress‐inducing substance towards rainbow trout.…”
Section: Discussionmentioning
confidence: 97%
“…Such changes have also been documented in fish exposed to diazinon, diclofenac, deltamethrin or heavy metals, that is well-known stressors or substances which are toxic to aquatic organisms (Tribskorn et al 2004;Cengiz & Unlu 2006;Vinodhini & Narayanan 2009). Interestingly, our earlier study demonstrated that KYNA has antioxidant properties in in vitro conditions, whereas in ex vivo circumstances, it stimulated oxidative processes (Małaczewska et al 2013 andMałaczewska et al 2014). This observation seems to confirm the above hypothesis that KYNA can be a toxic or stress-inducing substance towards rainbow trout.…”
Section: Discussionmentioning
confidence: 99%